Pengaruh Kejelasan Sasaran Anggaran, Pengendalian Akuntansi Dan Sistem Pelaporan Terhadap Akuntabilitas Kinerja Instansi Pemerintah Daerah Kabupaten Enrekang - Nurmin; Masyita, Siti (Insan Cita Bongaya Research Journal, 2023)
This study aims to determine and analyze the clarity of budget targets, accounting control and reporting systems on the accountability of the performance of local government agencies of Enrekang Regency. The sample in this study was as many as 50 people and used multiple linear regression test analysis. The results showed that both simultaneously and partially the clarity of the influence of Budget Targets, Accounting Control and Reporting Systems on the Accountability of Performance of Local Government Agencies of Enrekang Regency.which means the better the clarity of budget targets, Accounting Control and Reporting Systems, the Accountability of Government Agency Performance also increases, the r square value has a moderate magnitude because there are still respondents who answer neutral to all questions asked.